PEMBELAJARAN BERBASIS PORTOFOLIO UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS X MA NEGERI 2 METRO SEMESTER GENAP TAHUN PELAJARAN 2011/2012 - Ipriadi, Ipriadi; Muhfahroyin, Muhfahroyin (UNIVERSITAS MUHAMMADIYAH METRO, 2013)
Students learning outcomes is a change of the students Â based their esperienced, that is learning outcomes from learning process that the students doing while learning and appers from students showed by their score. This result got from students activity during learning process. The portofolio based learning demand students as self regulated learners and active in the learning process guided by teacher to gets learning purpose. The classroom action research was conducted in grade XG MAN 2 Metro academic year 2011/2012. The conclusion of this research was the portofolio based learning could increase the studentsâs achievement in Â grade XG MAN 2 Metro year 2011/2012 from the cycle I to the cycle II by 50% and researcher sugests that the portofolio based learning be able used to the increases the studentsâs achievement of biology learning.Â Kata kunci: Pembelajaran Berbasis Portofolio, Aktivitas Belajar, Hasil Belajar